STYLISTICALLY COMPLEX WORKS IN ENGLISH AND UZBEK PROSE - Normamatov Farrukh Komiljon ugli (Western European Studies, 2024)
this article investigates the concept of works written in a complex genre, stylistically complex works in English and Uzbek prose, their structures, the synthesis of traditional and modern methods used in the analysis of works, philosophical, psychological, cultural and historical researches
Keywords: complex work; symbolism; language and structure; intertextuality